Can the Inclusion of a Vegetable Biocholine Additive in Pig Feed Contaminated with Aflatoxin Reduce Toxicological Impacts on Animal Health and Performance? - Dazuk V.* (2023)
© 2023 by the authors.(1) Background: This study’s objective was to determine whether adding vegetable biocholine (VB) to pigs’ diets would minimize the negative effects caused by daily aflatoxin (B1 + B2) intake. (2) Methods: We used seventy-two whole male pigs weaned at an average of 26 days and divided them into four groups with six replicates each (2 × 2 factorial). The treatments were identified as Afla0VB0 (negative control, without aflatoxin and without VB); Afla500VB0 (positive control, 500 µg/kg of aflatoxins; Afla0VB800 (800 mg/kg of VB); and Afla500VB800 (500 µg/kg of aflatoxin +800 mg/kg of VB). (3) Results: In the first 20 days of the experiment, only the pigs from Afla500VB0 had less weight gain and less feed consumption, different from the 30th to 40th day, when all treatments had lower performance than the negative control. In the liver, higher levels of oxygen-reactive species and lipid peroxidation were observed in Afla500VB0, associated with greater activity of the enzymes alanine aminotransferase and aspartate aminotransferase. In the jejunum, oxidative stress was associated with nitrous stress in Afla500VB0. An increase in splenic glutathione S-transferase activity in the Afla500VB800 animals was observed. (4) Conclusions: Consuming a diet contaminated with 500 µg/kg of aflatoxin influences the health and performance in the nursing phase in a silent way; however, it generates high economic losses for producers. When VB was added to the pigs’ diet in the face of an aflatoxin challenge, it showed hepatoprotective potential.